Multispectral analysis of Nuragic metallic samples (Sardinia, Italy) - Lins, Sergio Augusto Barcellos (2020)
ABSTRACT: In this investigation, a protocol combining the use of Monte Carlo simulations together with energy-dispersive X-ray fluorescence (ED-XRF) analysis was used to determine the chemical composition of a set of nine objects from a private collection, apprehended by Carabinieri and without archaeological context. The artefacts are thought to belong to the nuragic period from Sardinia, Italy. The protocol employed is a powerful and non-destructive method useful for cultural heritage applications where usually no sampling is allowed and was applied here with the objective of attesting the authenticity of the objects. The samples were simulated as multilayered structures composed of bulk material and outer corrosion layer so the patina thickness and composition could be estimated as well by the Xray Monte Carlo (XRMC) package. The method proved useful and powerful, capable of efficiently determining the composition and structure of most of the objects in a total nondestructive approach, attesting the existence of at least one fake in the set. Nevertheless, for a more throughout evaluation and a better estimation of the patina composition, the use of complementary analytical techniques has shown required.